Sexism, fear of negative evaluation and destructive communication in the couple - Cruz Torres, Christian Enrique (2021)
Ambivalent sexism proposes that male hegemony is sustained through devotion to mothers, wives and carers and through hostility towards women who do not fulfill these roles. These patterns would increase violent communication to women, an effect that would be increased by individual differences such as fear of negative social assessment (TESN). We sought to identify the impact of TESN and the six components of ambivalent sexism on destructive communication styles in the couple, analyzing data from 590 young participants. Regressions and models of structural equations confirm effects of hostile sexism and TESN on destructive communication, but only for men. The effects of each component of ambivalent sexism on destructive communication are discussed.